2015
DOI: 10.1109/tmag.2015.2427115
|View full text |Cite
|
Sign up to set email alerts
|

Cogging Torque Mitigation in Axial Flux Magnetic Gear System Based on Skew Effects Using an Improved Quasi 3-D Analytical Method

Abstract: Since the flux leakage phenomenon is dominant in the inner and outer radii of axial flux magnetic gears (AFMGs), a prominent over estimation of torque prediction is obtained by 2D analytical method (AM) in comparison with 3D finite element method (FEM) simulations. The main motivation of this study is to present an improved quasi 3D analytical method (IQAM) which is an improvement and amendment of the 2D AM by a simple and effective radial dependence modeling of the axial and tangential magnetic field distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The flux is produced by the centric rotor with no load. The maximum magnetic flux density is near to 0.7 T. The shape is similar to the sine wave, and it can be easily observed that the slots and teeth on stator cause the distortion of the radial flux density wave [16]. Figure 10 presents the radial flux density distribution on the surface of the stator teeth over all of the poles.…”
Section: Flux Density On the Stator Teeth Endmentioning
confidence: 81%
“…The flux is produced by the centric rotor with no load. The maximum magnetic flux density is near to 0.7 T. The shape is similar to the sine wave, and it can be easily observed that the slots and teeth on stator cause the distortion of the radial flux density wave [16]. Figure 10 presents the radial flux density distribution on the surface of the stator teeth over all of the poles.…”
Section: Flux Density On the Stator Teeth Endmentioning
confidence: 81%
“…Despite these advancements, the design faced limitations in significantly boosting gear torque and exhibited magnetic leakage in slower-rotating rotors. Furthermore, the performance evaluation of AMGs necessitates the construction of complex three-dimensional models, a process that is notably time-consuming and has thus limited the proliferation of research and development in this area [24,25]. The axial-direction force exerted by AMGs also poses substantial challenges to their fabrication, complicating the design process further.…”
Section: Of 19mentioning
confidence: 99%
“…Hence, some methodologies used to improve operational performance of the radial‐flux FMMG can be also applied to the axial‐flux FMMG. For instances, skewing or pole pairing can be used to realize torque‐ripple depression [76, 77] and the Halbach PM array is effective to elevate the torque density [78].…”
Section: Development Of the Field‐modulated Magnetic Gearmentioning
confidence: 99%